Keberadaan Dan Penerapan Hukum Adat Di Tengah Sistem Pemerintahan Masyarakat Suku Baduy - Maranatha, Leona Citra; Kurniawan, Stanley; Selly, Jeane N. (Peneliti.net, 2023)
Banten Province is one of the provinces that has a customary law community that is still alive and developing today, namely the Baduy/Bedouin customary law community (Baduy tribe). The Baduy customary law community has social stratification or community stratification based on a certain status or level according to the agreement. They live in remote areas of customary land and still uphold the beliefs of Sunda Wiwitan. The Baduy tribe in their daily lives speak Sundanese and Indonesian. The Baduy tribe has a population of around 26,000 people consisting of inner Baduy and outer Baduy. Officially, recognition, acceptance or justification for the existence of indigenous peoples in the constitutional structure is regulated in Article 18 of the 1945 Constitution. The civilization of indigenous peoples has a long history in Indonesia. Indigenous peoples are a real segment of the Indonesian population. The existence of these provisions as an explanation of the status of indigenous peoples who have long been part of the Indonesian state. The enactment of 3 (three) legal sub-systems in the legal system in Indonesia, namely Western Law, Customary Law and Islamic Law since the independence of the Republic of Indonesia, on August 17, 1945 until now. This supports the existence of indigenous peoples as a historical reality that cannot be avoided or denied by the government.